Comparative Analysis of Fisheries Business in Selayar Regency: Reviewed From the Fundamental Aspect of Finance - Lailil, Dinar; Rustan, Rustan; Badollahi, Ismail (Borong Newinera Publisher, 2026)
This study aims to analyze and compare the financial performance of two fisheries businesses in the Selayar Islands Regency, namely CV. Sinar Jaya and CV. Yabba 505, based on fundamental financial aspects including accounts receivable turnover, liquidity, quality costs, and sales during the period 2021 to 2024. The method used is a quantitative approach with descriptive analysis and trend analysis, based on financial report data and interviews. The results show that CV. Sinar Jaya has relatively stable liquidity and sales management and improved efficiency in managing accounts receivable and quality costs. Meanwhile, CV. Yabba 505 experienced significant fluctuations in liquidity and accounts receivable turnover, despite recording higher annual sales growth in percentage terms. This study emphasizes the importance of integrated management of fundamental financial aspects to improve the competitiveness and sustainability of local fisheries businesses. These findings are expected to serve as a reference for business actors and policymakers in formulating strategies for developing MSMEs in the fisheries sector in the archipelago.